Impact of value co-creation on international customer satisfaction in the airsoft industry: Does country of origin matter? - Gabriela Menet; Marek Szarucki (Journal of Risk and Financial Management, 2020)
The paper's objective is to investigate the impact of value proposition co-creation on international customer satisfaction in the airsoft industry. This empirical paper aims at answering a question "Which factors influence satisfaction of the international customers involved in the process of value co-creation in the airsoft industry" and sets a hypothesis that value co-creators' country of origin has a positive impact on customers' satisfaction. A case study approach of an entrepreneurial company (GATE) was supplemented with data collected via a survey (n = 176), where consumers' perception of the firm's value proposition and its influence on their satisfaction were investigated. The study contributes to the value creation theory by identifying the main factors influencing customer satisfaction in the airsoft industry and verifying whether the co-creators' origin affects the factors' ratings. The results indicate that the most crucial factors influencing international customer satisfaction in this industry are quality level and product functionality and that the country of origin of customers has no significant impact on international customer satisfaction.
Keywords: 330; airsoft industry; country of origin; customer satisfaction; entrepreneurship; value co-creation; value proposition